2016
DOI: 10.1111/1365-2435.12753
|View full text |Cite
|
Sign up to set email alerts
|

The long and the short of it: a global analysis of hawkmoth pollination niches and interaction networks

Abstract: Summary 1. Proboscis length has been proposed as a key dimension of plant pollination niches, but this niche space has not previously been explored at regional and global scales for any pollination system. Hawkmoths are ideal organisms for exploring pollinator niches as they are important pollinators in most of the biodiverse regions of the earth and vary greatly in proboscis length, with some species having the longest proboscides of all insects. 2. Using datasets for nine biogeographical regions spanning the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
137
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(150 citation statements)
references
References 87 publications
9
137
3
1
Order By: Relevance
“…The nectar spurs of H. aitchisonii are much shorter than their pollinators’ proboscises, in contrast to previous studies on Habenaria , which indicated that only pollinators with proboscises roughly equal to or slightly shorter than the nectar spurs could ensure efficient pollinia transfer and reproductive success (Singer & Cocucci, ; Singer et al, ; Peter et al, ; Pedron et al, ; Xiong et al, ; Johnson et al, ; Zhang & Gao, ; Tao et al, ). In other words, the mechanical mismatch could result in an opposite situation in which visitors probe flowers without touching the column and removing pollinia.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…The nectar spurs of H. aitchisonii are much shorter than their pollinators’ proboscises, in contrast to previous studies on Habenaria , which indicated that only pollinators with proboscises roughly equal to or slightly shorter than the nectar spurs could ensure efficient pollinia transfer and reproductive success (Singer & Cocucci, ; Singer et al, ; Peter et al, ; Pedron et al, ; Xiong et al, ; Johnson et al, ; Zhang & Gao, ; Tao et al, ). In other words, the mechanical mismatch could result in an opposite situation in which visitors probe flowers without touching the column and removing pollinia.…”
Section: Discussioncontrasting
confidence: 61%
“…Previous investigations indicated that Habenaria species were predominantly pollinated by lepidopterans (Singer & Cocucci, ; Singer, ; Singer et al, ; Peter et al, ; Pedron et al, ; Ikeuchi et al, ; Xiong et al, ; Zhang & Gao, ; Tao et al, ), which usually have long proboscises. The pollinia in Habenaria species were observed to be placed on various sites on moths’ or butterflies’ bodies, such as on their eyes, heads, or at the base of their proboscises, depending on the match between the nectar spur and pollinator proboscis length (Singer & Cocucci, ; Singer et al, ; Peter et al, ; Pedron et al, ; Xiong et al, ; Johnson et al, ; Zhang & Gao, ; Tao et al, ). In Habenaria limprichtii Schltr., pollinia were observed attached to sphingids’ eyes but sometimes attaching to settling noctuid moths’ legs (Tao et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moth pollination has been considered to be relatively rare in the Asian flora (Corlett, ). However, it is reasonable to doubt this conclusion given that studies of nocturnal pollination by moths have been especially scarce in Asia (see the review by Johnson et al, ). Moreover, a number of moth flowers have been revealed there over the past few years, including some cases involving hawkmoths (Zhang et al, ; Mizusawa et al, ; Yokota & Yahara, ; Liu & Huang, ; Xiong et al, ; Yan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In a global scale morphometrics study, Johnson et al . () have analysed hawkmoth proboscis lengths, flower lengths and the degree of specialisation in nine biogeographical regions spread across the Old and New Worlds. At a regional level, proboscis lengths of hawkmoths show discontinuous frequency distributions which tend to be matched by tube lengths of the night‐opening flowers that they visit.…”
mentioning
confidence: 99%
“…The study of Johnson et al . () is particularly valuable for bringing together a large body of data on moth‐flower relationships (including analyses of pollen loads) collected across several species‐rich tropical regions.…”
mentioning
confidence: 99%